The Strategy of Taiwan Government to Build Muslim Friendly Environment - Mahendra, Zulfan Fakhri; Surwandono, Surwandono (State Islamic Institute of Kudus (IAIN Kudus), 2021)
Taiwan as a country which is nicknamed the country of Formosa or beauty has the potential to increase its capacity in tourism. Seeing the projection of the number of Muslims that has continued to increase. Taiwan developed its new south bound policy to attract Muslim people to travel and apply in Taiwan. Muslim Friendly Environment is a new breakthrough from Halal Tourism that many Muslim minority countries have conveyed. Through the Global Muslim Travel Index, Taiwan is in position 3 in the world as a Muslim Friendly region. Taiwanese strategies in their public diplomacy efforts in coordination with non-government actors such as the Muslim community. starting to continue to develop development to manage halal information that is able to bind more and more Muslims.